Strategi Komunikasi Media Relations dalam Menjaga Citra Perusahaan - 10080021319, Reidy Oktavianto Putra; Wiki Angga Wiksana (Bandung Conference Series: Public Relations, 2025)
Abstract. The world of professional sports positions corporate image as a crucial aspect that must be maintained, especially for major clubs like Persib Bandung that receive significant media exposure. The role of Public Relations is vital in fostering relationships with journalists to build a positive public perception. This study aims to examine the media relations communication strategy implemented by the Public Relations of PT. Persib Bandung Bermartabat in maintaining the company's image through relationships with journalists. This research uses a qualitative method with a case study approach. Data were collected through in-depth interviews with PR personnel and journalists. The findings show that Persib's PR builds trust through open, responsive communication and strong personal relationships. Media relations are carried out by ensuring smooth information distribution, effective issue management, and narrative construction aligned with the company’s image. In addition, the PR team conducts various media relations activities such as press conferences and media visits. They also provide facilities that support journalists’ work by offering easy access to information and maintaining opennessin communication. These strategies have proven effective in creating mutually beneficial professional relationships and maintaining Persib's image as a professional and credible club. Abstrak. Dunia olahraga professional memposisikan citra perusahaan menjadi aspek penting yang harus dijaga, terutama bagi klub besar seperti Persib Bandung yang memiliki eksposur tinggi di media. Peran Public Relations sangat vital dalam menjalin hubungan dengan wartawan guna membentuk persepsi publik yang positif. Penelitian ini bertujuan untuk mengetahui strategi komunikasi media relations yang dijalankan oleh Public Relations PT. Persib Bandung Bermartabat dalam menjaga citra perusahaan melalui relasi dengan wartawan. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Data diperoleh melalui wawancara mendalam dengan tim PR dan wartawan yang menjadi mitra kerja. Hasil penelitian menunjukkan bahwa PR Persib membangun kepercayaan melalui komunikasi yang terbuka, responsif, serta hubungan personal yang baik dengan wartawan. Proses media relations dijalankan dengan memastikan distribusi informasi yang lancar, pengelolaan isu yang tepat, serta penyusunan narasi yang sesuai dengan citra perusahaan. Selain itu, PR juga menjalankan berbagai aktivitas dan program media relations seperti press conference dan media visit. PR menyediakan fasilitas bagi media yang mendukung kelancaran kerja wartawan, dengan memberikan akses informasi yang mudah dan sikap terbuka dalam komunikasi. Strategi ini terbukti efektif dalam menciptakan hubungan profesional yang saling menguntungkan dan membentuk citra Persib sebagai klub yang profesional dan kredibel.